Biomaterial‐Interrelated Bacterial Sweeper: Simplified Self‐Assembled Octapeptides with Double‐Layered Trp Zipper Induces Membrane Destabilization and Bacterial Apoptosis‐Like Death. Issue 12 (14th November 2021) - Fang, Yuxin; Zhu, Yunhui; Li, Ling; Lai, Zhenheng; Dong, Na; Shan, Anshan
Abstract: Treatment of microbial‐associated infections continues to be hampered by impaired antibacterial efficiency and the variability in nanomedicines. Herein, an octapeptide library with a double‐layered zipper, constructed via a systematic arrangement, simplifying the sequence and optimizing the structure (diverse motifs including surfactant‐like, central‐bola, and end‐bola), is assessed in terms of biological efficiency and self‐assembly properties. The results indicate that peptides with double‐layered Trp zipper exhibit significant antimicrobial activity. Extracellularly, affinity interactions between micelles and bacteria induce the lateral flow of the membrane and electric potential perturbation. Intracellularly, lead molecules cause apoptosis‐like death, as indicated by excessive accumulation of reactive oxygen species, generation of a DNA ladder, and upregulation of mazEF expression. Among them, RW‐1 performs the best in vivo and in vitro. The intersecting combination of Trp zipper and surfactants possesses overwhelming superiority with respect to bacterial sweepers (therapeutic index [TI] = 52.89), nanostructures (micelles), and bacterial damage compared to RW‐2 (central‐bola) and RW‐3 (end‐bola). These findings confirm that the combination of double‐layered Trp zipper and surfactants has potential for application as a combined motif for combating microbial infection and connects the vast gap between antimicrobial peptides and self‐assembly, such as Jacob's ladder. Abstract : The micellar structure is formed by the self‐assembly forces of the antimicrobial peptides (AMPs) provided by the Trp zipper. Micelles have good biocompatibility and bacterial scavenging ability in vitro and in vivo. The bactericidal mechanism of the micelle is to form holes and interfere with potential in the bacterial membrane, leading to DNA breakage and apoptosis‐like death of the bacteria after entering the cell.